Experimental Investigation On Machining Performance of Ti6Al4V On Electro Discharge Machining Using Stationary and Rotary Electrode - K.M., Rajan; Routara, Bharat Chandra; Sahoo, Ashok Kumar; Satpathy, M.P. (International Journal of Integrated Engineering, 2023)
Titanium alloys are commonly used in different industries due to its high strength and less in weight. Even though the machinability of titanium alloys is very less, due to its high strength, it becomes more useful in aerospace and medical industries. In this study, the performance of stationary and rotary copper electrodes on machining of Titanium alloy Ti-6Al-4V with Electro Discharge Machining (EDM). Material removal rate(MRR), tool ware rate(TWR) and surface roughness(SR) were analyzed with three controllable input parameters such as pulse on time (Ton), Peak Current(Ip) and Gap Voltage (V). The design of experiment chosen for the experimentation as the Box-Behnken response surface design method. The results are analysed using grey relational analysis(GRA) coupled with firefly algorithm. In both the case of stationary and rotary electrode, it was revealed that gap voltage is significant for overall grey relational grade. The machining performance of Titanium alloy Ti-6Al-4V in the case of rotary mode of electrode is quite better as compare to the stationary mode of operation.